2017
DOI: 10.18066/revistaunivap.v23i43.365
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Da Resistência Aos Antifúngicos De Leveduras Isoladas De Candidúrias De Um Hospital De Médio Porte

Abstract: Resumo: Devido à alta incidência de infecções graves, tem se buscado novas terapias antifúngicas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…However, there have been reports of Candida spp. resistance to antifungals commonly used in clinical practice [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been reports of Candida spp. resistance to antifungals commonly used in clinical practice [29].…”
Section: Resultsmentioning
confidence: 99%
“…Worryingly, increased resistance to antifungal drugs threatens the effectiveness of treatments used to combat infections caused by this microorganism [ 60 ]. In this context, a study analyzing antifungal resistance in infections by Candida species, including C. albicans , in Brazilian hospitals recorded high rates of resistance to conventional antifungal agents such as fluconazole (88.89%), miconazole (66.67%), nystatin (55.56%), and amphotericin B (50.00%) [ 61 ]. Similar studies found resistance rates to fluconazole in C. albicans , ranging between 61% and 100% [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Devido ao fato de que esse esterol existe apenas na célula fúngica e não nas células de mamíferos, ele se torna um alvo seletivo para os antifúngicos, buscando-se, assim, novas substâncias que atuem especialmente no ergosterol, não causando efeito adversos nas células humanas. 26,30,31 Substâncias que atuam no ergosterol da membrana tendem a ligar-se no ergosterol exógeno, que está no meio enriquecido, desviando sua atividade do ergosterol da membrana fúngica. Consequentemente, será necessária uma maior quantidade da substância testada para inibir o crescimento fúngico da mesma quantidade de inóculo.…”
Section: Discussionunclassified